Benefits and potential trade-offs associated with yeast-like symbionts during virulence adaptation in a phloem-feeding planthopper - Horgan, Finbarr G.; Ferrater, Jedeliza B. (Wiley, 2017)
Insect herbivores form symbioses with a diversity of prokaryotic and eukaryotic microorganisms. A role for endosymbionts during host feeding on nutrient‐poor diets – including phloem – is now supported by a large body of evidence. Furthermore, symbiont‐herbivore associations have been implicated in feeding preferences by host races (mainly aphids) on multiple plant species. However, the role of symbionts in mediating herbivore preferences between varieties of the same plant species has received little research attention despite the implications for virulence adaptation to resistant crops. This study investigates the role of yeast‐like symbionts (YLS) in virulence adaptation and host plant switching among populations of the brown planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae), that were selected on various rice [Oryza sativa L. (Poaceae)] lines differing in their resistance against herbivores. Planthopper fitness (nymph weight) declined where YLS densities were depleted through heat treatment. However, compared to normal symbiotic planthoppers, the depletion of symbionts did not generally change the relative fitness of planthoppers (each ‘adapted’ to a single natal host) when switched to feed on a range of rice lines (exposed hosts). In some cases, this occurred despite differences in YLS density responses to the various hosts. Furthermore, we detected no fitness costs associated with YLS in adapted populations. Therefore, the results of this study suggest that, whereas YLS are essential for planthopper nutrition, changes in YLS density play little role during virulence adaptation and host plant switching by the brown planthopper.